A novel hyperactive variant of the Sleeping Beauty transposase facilitates non-viral genome engineering - Matthias Thomas Ochmann; Csaba Miskey; Lacramioara Botezatu; Nicolás Sandoval-Villegas; Tanja Diem; Zoltán Ivics (Elsevier, 2024)
The Sleeping Beauty (SB) transposon system is a useful tool for genetic applications, including gene therapy. We discovered a hyperactive variant of the SB100X transposase, called SB200X. This mutant, resulting from a specific amino acid replacement (Q124C), showed an ∼2-fold increase in transposition activity in various human and murine cells. Other amino acid replacements in position 124 also led to a hyperactive phenotype. Position 124 is located at the very edge of the linker region that connects the DNA-binding and catalytic domains of the transposase. Consistent with a role of the linker in an autoregulatory mechanism called overproduction inhibition (OPI) in the monophyletic group of mariner transposases, we show that the hyperactivity of Q124C manifests at high concentrations of the transposase, suggesting a partial resistance of SB200X to OPI. We demonstrate that the hyperactive phenotype of Q124C can be combined with features of other useful mutations in the SB transposase. Namely, Q124C improves the transposition efficiency of the previously described K248R variant, while maintaining or even slightly improving its safer genome-wide integration profile. The SB200X transposase could enhance the utility of SB transposon-mediated genome engineering in preclinical and clinical applications.